1836 Tex. Gen. Laws 54-55, An Act to Provide for the National Defense by Organizing the Militia, § 1. - (:unkn) unknown (My University, 1836)
That every citizen so enrolled and notified, shall within ten days thereafter provide himself with a good musket, a sufficient bayonet and belt, six flints, knapsack and cartridge box, with twenty-four suitable ball cartridges
Keywords: ARMED FORCES